NiCo2S4 Nanocrystals on Nitrogen-Doped Carbon Nanotubes as High-Performance Anode for Lithium-Ion Batteries - Haisheng Han; Yanli Song; Yongguang Zhang; Gulnur Kalimuldina; Zhumabay Bakenov (Springer Science and Business Media LLC, 2021)
In recent years, the development of lithium-ion batteries (LIBs) with high energy density has become one of the important research directions to fulfill the needs of electric vehicles and smart grid technologies. " "Nowadays, traditional LIBs have reached their limits in terms of capacity, cycle life, and stability, necessitating their further improvement and development of alternative materials with remarkably enhanced properties. " "A nitrogen-containing carbon nanotube (N-CNT) host for bimetallic sulfide (NiCo2S4) is proposed in this study as an anode with attractive electrochemical performance for LIBs. " "The prepared NiCo2S4/N-CNT nanocomposite exhibited improved cycling stability, rate performance, and an excellent reversible capacity of 623.0 mAh g–1 after 100 cycles at 0.1 A g–1 and maintained a high capacity and cycling stability at 0.5 A g–1. " "The excellent electrochemical performance of the composite can be attributed to the unique porous structure, which can effectively enhance the diffusivity of Li ions while mitigating the volume expansion during the charge–discharge processes.
Keywords: Materials science; Anode; Lithium (medication); Carbon nanotube; Electrochemistry; Nanocomposite; Nanotechnology; Composite number; Nanochemistry; Chemical engineering; Bimetallic strip; Carbon fibers; Electrode; Composite material; Metallurgy; Chemistry; Medicine; Metal; Physical chemistry; Engineering; Endocrinology; type of access: open access